Analisis Pengaruh Temperatur, pH dan Laju Alir Terhadap Pembentukan Scale - Mawar Marbun; Nijusiho Manik, S.T., M.T; Abdul Gafar Karim (Lembaran publikasi minyak dan gas bumi, 2025)
The LMN-47 well has the highest scale formation potential compared to other wells in the X field with the highest Scale Index value of 1.39. The condition of this well is also different because the scale formation only occurs in the tubing perforate compared to other wells where scale formation occurs in all pump circuits. The scale formation mechanism is closely related to the content of the formation water and is influenced by temperature, pH, and flow rate parameters. Therefore, testing is needed to determine the scale formation with temperature, pH, and flow rate parameters that are in accordance with the actual conditions in the well through a scale simulator tool. From the simulation on the scale simulator tool designed with a flow rate of 15.2279 liters/minute, pH 7.99 and temperature 56.29 oC, 6.14 grams of carbonate scale (CaCO3) were formed. The results of the analysis proved that the higher the temperature, the faster the growth rate of carbonate scale (CaCO3), the more alkaline the pH, the faster the scale will grow, as well as the flow rate which is directly proportional to temperature and pH.